1986
DOI: 10.1042/bj2370567
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the reduction of neutrophil cytochrome b-558 by dithionite

Abstract: The reduction with dithionite of neutrophil cytochrome b-558, implicated in superoxide generation by activated neutrophils, was investigated by a stopped-flow technique in non-ionic-detergent extracts of the membranes and in crude membrane particles. The dependence of the pseudo-first-order rate constants on the concentration of dithionite was consistent with a mechanism of reduction that involves the dithionite anion monomer SO2.- as the reactive species. The estimated second-order rate constant was 7.8 X 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The interpretation is clarified by another study that showed dithionite does not dissociate an analogous dimeric Grx–iron–sulfur complex under anaerobic conditions [39] .Therefore the most likely mechanism by which dithionite promotes dissociation of the dimeric Grx2 complex is by donating an electron to molecular oxygen to form superoxide which then acts as a one electron oxidant as shown in Scheme 1 . This conclusion is supported also by previous studies that documented formation of radicals (superoxide) when dithionite was added to aqueous solutions under aerobic conditions [65–67] .…”
Section: Discussionsupporting
confidence: 87%
“…The interpretation is clarified by another study that showed dithionite does not dissociate an analogous dimeric Grx–iron–sulfur complex under anaerobic conditions [39] .Therefore the most likely mechanism by which dithionite promotes dissociation of the dimeric Grx2 complex is by donating an electron to molecular oxygen to form superoxide which then acts as a one electron oxidant as shown in Scheme 1 . This conclusion is supported also by previous studies that documented formation of radicals (superoxide) when dithionite was added to aqueous solutions under aerobic conditions [65–67] .…”
Section: Discussionsupporting
confidence: 87%
“…The observed rate constant ( k obs ) did not increase linearly with the concentration of dithionite. Instead, as with other heme proteins, the k obs showed a dependence on the square root of the dithionite concentration (Figure B) and plots of k obs versus [dithionite] 1/2 were linear (Figure B, inset). These results are consistent with the reductant being the sulfur dioxide radical anion (SO 2 •– ), formed by rapid homolysis of dithionite as described by eqs and . normalS 2 normalO 4 2 2 SO 2 Fe(III)‐CBS + SO 2 Fe(II)‐CBS + SO 2 The forward and reverse rate constants for eq are as follows: k 1 = 2.5 s –1 , and k –1 = 1.8 × 10 9 M –1 s –1 (25 °C). , This mechanism yields k obs as described by eq , where k 2 is the second-order rate constant for reduction of Fe(III)-CBS by SO 2 •– k obs = k 2 false( k 1 / k 1 false) 1 / 2 false[ normalS 2 normalO 4 2 false] 1 / 2 From the fit of the values of k obs to eq (Figure B), the dependence on [S 2 O 4 2– ] 1/2 was found to be k 2 ( k 1 / k –1 ) 1/2 = 353 ± 7 M –1/2 s –1 an...…”
Section: Resultsmentioning
confidence: 76%
“…•¯ as the reducing agent (53)(54)(55)(56)(57)(58). Detailed analysis of the kinetics of reduction of P450 cam by dithionite was published by Hintz and Peterson (59), who found the mechanism of this reaction to involve SO 2 •¯ as the reducing species.…”
mentioning
confidence: 99%
“…Studies of the kinetics of reduction by dithionite were employed to probe apparent conformational transitions and changes in the ligand sphere of the heme iron in such heme-containing enzymes as bovine heart cytochrome c oxidase ( , ), cytochrome bo from Escherichia coli ( , ), and some other biological electron carriers ( ). For most heme proteins studied it was shown that the mechanism of reduction involves the dithionite anion monomer SO •- 2 as the reducing agent ( ). Detailed analysis of the kinetics of reduction of P450 cam by dithionite was published by Hintz and Peterson (), who found the mechanism of this reaction to involve SO •- 2 as the reducing species.…”
mentioning
confidence: 99%